Does Incentives and Job Satisfaction Improve Employee Performance? - Syamsul Alam; Syamsul Ridjal; Edy Jumady; Anita Idris (Enrichment : Journal of Management, 2023)
This study aims to test and examine the effect of incentives and job satisfaction on employee performance at the Makassar City Regional Planning and Development Agency Office. This study was conducted at the Makassar City Regional Planning and Development Agency Office. This study involved 53 respondents from civil servants from the Makassar City Regional Planning and Development Office. This study uses primary data collected using a questionnaire. Furthermore, the data were analyzed using the statistical tool SPSS 22.0 using multiple regression analysis method. The data is tested through several stages of testing such as validity, reliability, classical assumption tests. Furthermore, to prove the hypothesis proposed in this study will be seen through the coefficient of determination test, partial test (t-test). The results of this study indicate that incentives have an effect on employee performance, and job satisfaction has an effect on employee performance.